Desain UI/UX Aplikasi E-Commerce Berbasis Mobile pada DK Tou Variasi Memanfaatkan Figma - Putra, Wahyu Rahmana; Saputri, Nurul Adha Oktarini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
DK TOU Variasi is a business that offers and serves maintenance services and sells car variation tools. DK TOU Variation wants to develop its business in the era of information technology. Therefore, as a solution, the first step is to create a UI/UX design. In designing a mobile application, UI / UX is one of the main factors so that users are comfortable when using the application. One of the tools that can be used in the UI/UX design process is Figma. Figma itself is an online prototyping platform that can be used to design UI/UX for a web or mobile application. User centered design is a suitable method in making UI/UX, this method will interact directly with the user so that it can find out the wishes of the user.